An In‐Depth Seismological Analysis Revealing a Causal Link Between the 2017 MW 5.5 Pohang Earthquake and EGS Project. Issue 12 (14th December 2019) - Woo, J.‐U.; Kim, M.; Sheen, D.‐H.; Kang, T.‐S.; Rhie, J.; Grigoli, F.; Ellsworth, W. L.; Giardini, D.
Abstract: Hydraulic injection by the Pohang enhanced geothermal systems (EGSs) has been suspected to trigger the 2017 moment magnitude (MW ) 5.5 Pohang earthquake in South Korea. The last stimulation experiment in the EGS was conducted only 2 months before the disaster, which has led to this suspicion. In this study, we conducted a seismic analysis on the earthquakes that have occurred around the EGS site in the past 10 years. The study included the construction of a velocity model, earthquake detection, the determination of hypocenters, magnitudes, focal mechanisms, and stress inversion, and a clustering analysis. No seismic activity was detected near the study area until November 2015 when there was a loss of a large quantity of heavy drilling mud. For three stimulations of a geothermal well, earthquakes sequentially migrated to the southwest along a fault plane, leading to the location of the mainshock. The delineated fault plane crossed the injection well at approximately 3, 800 m, which corresponds to the borehole interval of not only the mud loss but also the breakage of the well's casing due to the mainshock rupture. These findings can be treated as empirical evidence for the hypothesis that the 2017 MW 5.5 Pohang earthquake was initiated on a critically stressed fault zone by the anthropogenic activity of fluid injection, consequentially releasing accumulated strain energy via tectonic loading. Key Points: On 15 November 2017, an MW 5.5 earthquake, one of the most devastating seismic events since the previous century, struck South Korea The 2017 MW 5.5 Pohang earthquake occurred in a fault zone reactivated by fluid injection into a geothermal well Heavy mud was lost from the fault zone during drilling, causing nearby microseismicity